PROBLEMATIKA PEMBELAJARAN BAHASA ARAB KURIKULUM 2013 - Wibowo, Fatih Rizqi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
This research is aimed to describe how arabic learning by using 2013 curriculum took place, what that causes the problem, and effort performes by teacher in MAN 2 Wates. This research becomes a measuring rod in developing 2013 curriculum -especially in arabic subject- and in increasing the success of arabic learning process.